Implementasi Jaringan Virtual Private Network (VPN) Menggunakan Protokol EoIP - Herman Kuswanto (LPPM Universitas Bina Sarana Informatika, 2017)
Abstract—The need for interconnection between networks will be needed, especially in a company that has many branches, but the company usually requires a minimum use of resources in order to obtain maximum results. To overcome these problems, we need a network of Virtual Private Network (VPN) using the protocol EoiP, Ethernet over Internet Protocol (EoIP) is a protocol in RouterOS that serves to build a Network Tunnel between MikroTik Router over a TCP / IP connection is by take advantage of the internet connection as the connecting.Keywords: Virtual Private Network, EoIP